Konsep Kepemimpinan: Pengertian, Sebab Munculnya, Sifat, dan Tipe Pemimpin - Muhammad Firdaus; M. Imamul Muttaqin (Student Research Journal, 2024)
Leadership is a crucial process within organizations, encompassing influence, motivation, and coordination to achieve collective goals. Leaders are not solely responsible for self-management but also guide others through skills in directing and inspiring actions. This paper discusses leadership definitions, origins, traits, and styles. Leadership theories, including the genetic theory emphasizing natural talent and the social theory prioritizing education and experience, are explored. Effective leadership depends on key characteristics such as intelligence, responsibility, honesty, and fairness. Leadership styles, like autocratic and laissez-faire, reveal contrasting approaches: one marked by strict control, the other by substantial freedom for subordinates. Ideal leadership balances situational and organizational needs to ensure efficient goal achievement.